2013
DOI: 10.1016/j.ijintrel.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of cultural dimensions of international and Dutch students on academic and social integration and academic performance in the Netherlands

Abstract: A common belief among educators is that international students are insufficiently adjusted to higher education in their host country, both academically and socially. Furthermore, several groups of international students experience considerable amounts of stress while adapting to the culture of the host-institute, but limited research has addressed whether and how transitional issues influence academic performance. In a cross-institutional comparison among 1275 students at nine higher educational institutes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 54 publications
4
77
4
1
Order By: Relevance
“…Our study suggests that cultures where relationships between subordinated and ordinates (e.g., bosses and employees and teachers and students) are perceived as more equal foster higher belongingness than cultures where there is strict hierarchy. Our findings are also in agreement with a recent Dutch study which found that international students from high power distance countries reported lower social adjustment and attachment to the educational institutions than students from low power-distance countries (Rienties and Tempelaar, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study suggests that cultures where relationships between subordinated and ordinates (e.g., bosses and employees and teachers and students) are perceived as more equal foster higher belongingness than cultures where there is strict hierarchy. Our findings are also in agreement with a recent Dutch study which found that international students from high power distance countries reported lower social adjustment and attachment to the educational institutions than students from low power-distance countries (Rienties and Tempelaar, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Although Hofstede's dimensions were derived from data gathered at the work place, they have been used in multiple studies examining cultural differences in schooling. The dimensions have been found to have predictive power in academic adjustment and social integration (Rienties and Tempelaar, 2013), learning style preference (Sugahara and Boland, 2010), and school principals' reports of aggressive behavior among students (Bergmüller, 2013). In line with these studies, we argue that school is an example of an organizational context which differs from culture to culture in exactly the same way as work place context.…”
Section: Cultural Dimensions Theorysupporting
confidence: 71%
“…While extensive research on internationalisation is available regarding how individual characteristics, such as academic integration (Rienties et al, 2011;Zepke & Leach, 2005), learning styles (De Vita, 2001;Joy & Kolb, 2009;Tempelaar et al, 2012), personal-emotional adjustment, stress and anxiety (Rienties & Tempelaar, 2013;Russell et al, 2010;Ward et al, 2005;Ward, Okura, Kennedy, & Kojima, 1998), influence how international students learn, adapt and adjust to the host-institute (See also recent reviews by Zhou et al (2008) and Volet & Jones, 2012). A limited number of studies have focussed on how social (learning) relations of international and host students influence how they learn in and outside the classroom.…”
mentioning
confidence: 99%
“…Students moving overseas face several challenges and the new environment will affect their AP. It is commonly perceived that international students were insufficiently attuned to the education system in their host country, concerning their academic and social domains and performed lesser than the local students (Rienties et al, 2012;Rienties & Tempelaar, 2013).…”
Section: Introductionmentioning
confidence: 99%